Tiers in-croyables: Michel de Certeau et Jeanne Favret-Saada en perspective - Gonzalez, Philippe (ThéoRèmes, 2025)
Michel de Certeau and Jeanne Favret-Saada investigated situations in which the plausibility of institutions guaranteeing social credibilities was collapsing. Working on related objects, they developed analogous approaches, attentive to actors' lived experience, to the grammars shaping their activities, and to the forms of social order these grammars presupposed or helped establish. A decisive divergence nonetheless appears in their respective understandings of the third party: absent in Certeau, opening the collective to its own transcendence; saturated in Favret-Saada, closing the group back upon itself. This difference reshapes how to conceive what actors can do, how the common is composed, how positions vis-à-vis others are defined, how conflicts are handled, and how critique may open new horizons.